Analisis Kepuasan Peternak Sapi Perah Anggota Koperasi Terhadap Dana Kesejahteraan Ternak (Survei di TPK Warnasari Kecamatan Pangalengan Kabupaten Bandung) - Bernadine , Agnia Paradisa; Nurlina, Lilis; Fitriani, Anita (Universitas Pahlawan Tuanku Tambusai, 2024)
The dairy cattle farming business can experience risks leading to significant losses, such as livestock mortality. Members of KPBS Pangalengan have a risk protection guarantee for their livestock business in the form of a program similar to insurance, namely the Livestock Welfare Fund (DKT). This study aims to analyze the satisfaction level of cooperative member dairy farmers with the services provided by DKT. The research was conducted from February to March 2024 at TPK Warnasari, Pangalengan District, Bandung Regency. Primary data was obtained from direct interviews with 43 respondents. Secondary data were collected from relevant agency documents. Analysis of data using Importance Performance Analysis (IPA) and interval scale. The results showed that the attributes requiring primary improvement in performance include the adequacy of claim compensation coverage, the suitability of DKT service coverage for farmers, and the completeness of health facilities for farmers. The satisfaction level of farmers was categorized as